Inovasi Eko-Sabun Berbasis Eco-Enzyme sebagai Solusi Pengurangan Sampah Organik di Desa Danawinangun dan Desa Kanci, Cirebon - Firasati, Aoliyah; Bukhori, Bukhori; Irvan, Muhammad; Permana, M. Septian Arya; Francisko, Muhamad; Salsabilla, Putri; Demiyati, Eba; Chaniago, Pedro Revosky (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This Community Service Program (PKM) demonstrates a community-based circular model for reducing household organic waste through the following flow: organic waste bank ? eco-enzyme ? eco-soap ? non-commercial testing education. The intervention was implemented for approximately two months in Danawinangun Village, Klangenan District (Cirebon Regency) as the pilot location; the resulting tools were packaged into a Replication Kit for Kanci Village, Astanajapura District (dissemination replication baseline). The evaluation design was descriptive pre-post, including 4–6 training sessions (production SOP, K3, and QC), production of ?4 test batches, and household use testing labeled “Test Samples Not for Sale”.  The results show an increase in partner capacity: pre–post knowledge/skills 47.8 ? 82.4/100, 87% of participants passed the practical test, and SOP/K3 compliance was 92%. Product quality performance was stable: pH 7.5–8.0 (household cleaner/dishwash variants), foam stability ?24 hours, consistent viscosity through gradual addition of NaCl following the salt curve. Usability test (n=120 samples; 80% response rate) resulted in good acceptance (74% rated ?4/5). Early impact on household behavior (n=84) showed organic waste separation +29 points, reduction in burning ?23 points, and ownership of organic waste containers +29 points. Local institutions (Team Decree, weekly meetings, Log/QC/Batch Card forms) ensured traceability and rapid learning. Findings confirm that a simple, standardized, participatory upstream approach is feasible in the short term and ready for replication through the Kanci Replication Kit, without transactional elements in the initial phase.ABSTRAKProgram Pengabdian kepada Masyarakat (PKM) ini menunjukkan model sirkular berbasis komunitas untuk pengurangan residu organik rumah tangga melalui alur bank sampah organik ? eco-enzyme ? eko-sabun ? uji guna non-komersial edukasi. Intervensi dilaksanakan selama ±2 bulan di Desa Danawinangun, Kec. Klangenan (Kab. Cirebon) sebagai lokasi pilot; perangkat hasilnya dikemas menjadi Replication Kit bagi Desa Kanci, Kec. Astanajapura (diseminasi baseline replikasi). Desain evaluasi bersifat deskriptif pra–pasca, mencakup pelatihan 4–6 sesi (SOP produksi, K3, dan QC), produksi ?4 batch uji, serta uji guna rumah tangga berlabel “Sampel Uji Tidak untuk diperjualbelikan”. Hasil menunjukkan peningkatan kapasitas mitra: pre–post pengetahuan/keterampilan 47,8 ? 82,4/100, 87% peserta lulus uji praktik, dan kepatuhan SOP/K3 92%. Kinerja mutu produk stabil: pH 7,5–8,0 (varian household cleaner/dishwash), stabilitas busa ?24 jam, viskositas konsisten melalui penambahan NaCl bertahap mengikuti salt curve. Uji guna (n=120 sampel; respon 80%) menghasilkan keterterimaan baik (74% menilai ?4/5). Dampak dini perilaku rumah tangga (n=84) menunjukkan pemilahan organik +29 poin, penurunan pembakaran ?23 poin, dan kepemilikan wadah organik +29 poin. Kelembagaan lokal (SK Tim, rapat mingguan, formulir Log/ QC/ Kartu Batch) memastikan traceability dan pembelajaran cepat. Temuan menegaskan bahwa pendekatan hulu, sederhana, terstandar, dan partisipatif layak diterapkan dalam horizon singkat serta siap direplikasi melalui Replication Kit Kanci, tetap tanpa unsur transaksi pada fase awal.